Air Operations in Israel's War Against Hezbollah Learning from Lebanon and Getting It Right in Gaza - Lambeth, Benjamin S. (RAND Corporation, 2011)
Examines the inconclusive results of the Israeli Defense Forces' operation in Lebanon after Hezbollah abducted two Israeli soldiers in 2006, which many believe represents a "failure of air power." The author demonstrates that this is an oversimplification of a more complex reality and contrasts the operation with Israel's counteroffensive against Hamas in the Gaza Strip in December 2008 and January 2009.